Conhecimentos tradicionais : direito à proteção e proteção aos direitos - Costa, Sebastião Patrício Mendes da (2017)
The present work addresses cultural rights and seeks to investigate the protection of traditional knowledge. Increased interest in traditional knowledge by multinational biotechnology companies, and by people in developing countries, who use so-called traditional medicine and other traditional knowledge, reinforces the need to protect this knowledge in order to preserve it and to allow a fair distribution of benefits among its holders. Environmental management is also equally favored with the use of traditional knowledge together with scientific knowledge, which help preserving biodiversity. In the democratic regime, the coexistence of different groups reinforces plurality of ideas and cultural diversity. Traditional knowledge is a product of cultural diversity and reflects deep cultural differences, based on the worldviews of distinct social groups. In this work, the effectiveness of the protection of traditional knowledge was investigated through research carried out in an interdisciplinary perspective, using a diversity of sources, in order to understand as fully as possible the protection of culture and traditional knowledge. To this end, the work counted on the contributions of Law and Anthropology, in order to understand the culture and traditional knowledge and to analyze the protection of this knowledge, which is a product of the cultural identity of indigenous peoples and traditional communities. One also considered notions of Economics in order to understand the economic reasons for the interest in this knowledge. The research examined studies by authors from various regions of the world and from different specialties. Among them, the authors of Latin America, especially those of indigenous origin, stand out. The indigenous contribution in research is present at various times and complements the work with the vision of indigenous peoples and traditional communities. After extensive analysis of the protection of traditional knowledge, it was verified that such protection is not effective in Brazil, despite having recent legislation on the subject, even with the various articles of the Federal Constitution that ensure the right to culture and respect for traditional communities and indigenous peoples, even though Brazil is a signatory of relevant international treaties that protect these traditional knowledge and practices. The lack of effective protection of traditional knowledge happens for at least three reasons: 1) For the lack of effective participation of indigenous peoples and traditional communities in public policies and other matters of their interests, as verified during the process of Law no. 13.123/15, the new Brazilian biodiversity law; 2) Brazilian legislation has not concerned itself with indigenous peoples and traditional communities living simultaneously in several countries. It did not even waved to protect the knowledge produced by them or the way in which the benefits would be distributed in that situation; 3) The Brazilian policy of protection of traditional knowledge is unrelated to territorial politics. The territory has a strong connection with the identity of indigenous peoples and traditional communities, and it is there that this knowledge develops. The Brazilian regression in relation to indigenous lands and traditional communities negatively affects the production and transmission of traditional knowledge for future generations.